O016 Exploring the drivers of geographic variation for paediatric tonsillectomy and adenoidectomy. (7th October 2021) - Tran, A; Liew, D; Horne, R; Rimmer, J; Nixon, G
Abstract: Introduction: Tonsillectomy and/or adenoidectomy (A/T) is first-line treatment for paediatric obstructive sleep apnoea. Provision of A/T is of critical interest to sleep medicine practitioners. Geographic variation of A/T has been described since the 1930s, but no studies have investigated the reasons behind it. This study aimed to describe the geographical distribution of paediatric A/T and investigate area-level factors associated with this variation. Methods: Linked administrative datasets captured a complete state-wide population of paediatric A/T performed between 2010 and 2015. Surgery data were collapsed by patient residence to the level of Local Government Area. Regression models were used to investigate the association between likelihood of surgery and area-level factors. Results: There was a 10.2-fold difference in A/T rates across the state, with higher rates more common in regional than metropolitan areas. Area-level factors associated with geographic variation that increased the likelihood of A/T were a higher proportion of children aged 5–9 years (IRR 1.07, 95%CI 1.01–1.14, P=0.03), while a higher proportion with low English-language proficiency (IRR 0.95, 95%CI 0.90–0.99, P=0.03) decreased the likelihood of A/T. In a sub-population of public sector surgeries, low maternal educational attainment increased the likelihood of A/T (IRR 1.09, 95%CI 1.02–1.16, P<0.001) and longer surgical waiting time reduced it (IRR 0.996, 95%CI 0.99273–0.99997, P=0.048). Discussion: Significant variation in surgery rates exist by geographical area state-wide, with factors analysed having significant impacts. These findings suggest that improved surgical access and better community understanding of the indications for A/T could decrease geographic variation.